Evaluating the Quality of the Inputs of Educational Administration in Master Degrees - Bijan Abdollahi; maryam eyni; Yasin Saeedi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Improvement and development of educational systems and programs to meet the challenges ahead of the main objectives and policies of the authorities of higher education seem to be crucial. The purpose of this study was to evaluate the quality of inputs of Educational Administration field in master degrees. The research method was survey research and applied.. The statistical population consisted of the whole body of the faculty, heads of departments, and the students of the academic year 2013-2014 (the third and fourth semester students) of state universities in Tehran. The research tool was a researcher-made questionnaire, the validity of whcih was determined by experts, and its Cronbach's alpha reliability index was .94 which is an acceptable level. To analyze the data, the chi-square test and standard of judgment were applied. The results showed that the overall quality of such factors as: the characteristics of heads of departments, their performance from the perspective of the faculty members, and the characteristics of the faculty members are favorable. Besides, the quality of students’ characteristics is in a fairly appropriate level, but students’ motivation is very low. Moreover, the results indicated that there is a mismatch between  goals and policies and educational and research facilities and faculty members’ and students’ needs. There is also incongruity between curriculum content and students’ needs in society., In the light of the results, it is suggested that some changes should be considered in the curriculum content so as to avoid repetitive content in the master degrees.